Effect of foot care health training towards nurses and health volunteers ability in performing foot care on diabetes in Batua Health Center, Makassar - Elly Lilianty Sjattar; Abdul Majid; Saldy Yusuf; Yuliana Syam; Nurhaya Nurdin (Journal of Health Science and Prevention, 2019)
Foot care is one of the management for diabetes mellitus that is important to prevent diabetes ulcers. Studies have proven that people with diabetes will have a lower risk of having diabetes ulcer if they have received health education about foot care to prevent diabetes ulcers Thus, health education is considered very important to help people with diabetes preventing foot ulcer. Health care provider including health professionals and health volunteers should provide health education regularly to the patient, however, due to their workload preventing them from providing this intervention to the patient as well as a lack of knowledge about foot care. Based on the initial interview with diabetes program staff, the health education program is not implemented well yet and they need specific training about foot care for nurses, health volunteers and patients. The aim of this study is to see the effect of foot care health training towards nurses and health volunteers ability performing foot care on diabetes. This study used pre-experimental with pre-test and post-test one-group design to 30 respondents (23 health volunteers and 7 nurses from Puskesmas Batua Makassar). The training was given the research team, and after training, there was follow-up training (two times) where the research team accompanied the respondents to provide foot care to the patients which was assessed through a questionnaire. Data were analysed using the paired t-test.This study found there is an improvement in ability in conducting diabetes foot care among the participants the average before treatment(x = 17.93, SD = 1.363) to (x = 19.37, SD = 0.718) after training. This study has proven the effect of training to improve nurses and health volunteers ability in performing foot care on diabetes patient. Thus, it is recommeded that nurses and health volunteers regularly providing health education related to foot care for diabetes patients to prevent foot ulcer such as including it in Prolanis health education program.